Use of wood-plastic composites in 4D printing technology - Daša Krapež Tomec; test test; Aleš Straže; Matevž Kokot; Manja Kitek Kuzman; Mirko Kariž (Les)
Three-dimensional (3D) printing with wood-plastic composites is already well known, and the use of wood in four-dimensional (4D) printing is being increasingly explored. 4D printing is an evolving area of additive technologies where, with the appropriate design of 3D printing and use of appropriate materials, we can create products that change shape and form dynamic structures when triggered externally. In 4D printing, the hygroscopicity of wood – usually considered a disadvantage – can be used as a positive property to design products that change their shape according to climatic conditions, especially humidity.